State-of-the-art of membrane flux enhancement in membrane bioreactor. Issue 1 (1st January 2018) - Kulesha, O.; Maletskyi, Z.; Ratnaweera, H.
Abstract: Membrane bioreactor (MBR) is a progressive alternative to conventional waste-water treatment. However, membrane fouling is one of the most significant barriers to further development of the MBR technology since it has a detrimental effect on system performance and stability. Therefore, a number of studies have been developed to comprehend the fouling nature and distinguish the effective flux enhancers, so as to develop a highly effective fouling control strategy. Key findings of these studies are summarized in the current review. Polysaccharides, proteins and humic substances tend to play the prime role in inducing fouling. The main factors affecting fouling behaviour in MBRs are membrane characteristics, membrane operation conditions and activated sludge properties, and recent evidence points out that the modification of the biomass characteristics with the use of chemical agents and adsorbents is among the most efficient fouling-hindering techniques. The current review not only aims to provide a comprehensive overview of the up-to-date methods of fouling alleviation using membrane flux enhancers in MBR but also intends to shed light on the mechanisms of their action, which, together with the experience of previous findings, can be the basis for developing a new advanced fouling mitigation strategy.